2021
DOI: 10.1101/2021.12.03.470951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of intron-1 of odorant-binding protein-1 of Anopheles stephensi as a marker for the identification of biological forms or putative sibling species

Abstract: Background: Anopheles stephensi, an invasive malaria vector, has been reported to have three biological forms identifiable based on the number of ridges present on the egg floats and the dimension of eggs. Recently, these forms have been designated as sibling species based on the fixed differences in the DNA sequence of the first intron of the odorant-binding protein-1 (AsteObp1). In this study, we evaluated the utility of this neutral marker in designating sibling species or identifying biological forms. Meth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…stephensi populations (insectary-colonized and wild populations) that were collected from 5 different locations, we found that most of the individuals from the wild had the SNP (G) in AsteObp1 (intron I Position 91bp) reported to be diagnostic of the type form, 18/105 individuals had an A at this same position, 18/105 had an A/G and 1/105 had an A/C in that position, likely representing population-level variations that have not been reported earlier (unpublished data). Also, many of the other markers are not universal and may vary from region to region and cannot resolve the biological forms accurately [56]. Here, we clearly demonstrate that the number of egg ridges is the gold standard and applicable marker to develop isofemale lines.…”
Section: Variations In Vector Competence Among the Biological Formsmentioning
confidence: 69%
“…stephensi populations (insectary-colonized and wild populations) that were collected from 5 different locations, we found that most of the individuals from the wild had the SNP (G) in AsteObp1 (intron I Position 91bp) reported to be diagnostic of the type form, 18/105 individuals had an A at this same position, 18/105 had an A/G and 1/105 had an A/C in that position, likely representing population-level variations that have not been reported earlier (unpublished data). Also, many of the other markers are not universal and may vary from region to region and cannot resolve the biological forms accurately [56]. Here, we clearly demonstrate that the number of egg ridges is the gold standard and applicable marker to develop isofemale lines.…”
Section: Variations In Vector Competence Among the Biological Formsmentioning
confidence: 69%